The Ability of Students in Using English Adverbs at State Politechnic of Pangkajene Kepulauan - Yusri Muhammad Yusuf; Bj Pratiwi (Hasanuddin University, 2019)
This research is about the ability of the first year students of the Agribusiness Department in using English adverb. Based on it, it is present two problems namely: 1) How is the ability of the first year Students of the Agribusiness department in using English adverb? 2) What are the factors influencing the students’ ability in using adverbs?. To answer the question above, the writer collects data by using test and questionnaire. The data collected through the instruments were analyzed by using descriptive analysis. The result of the research shows that some of the students in Agricultural State Polytechnic of Pangkep were less interested in English, especially in using adverbs. The first year Students of the Agribusiness department can only be classified into poor. This achievement was influenced by the low of the students’ interest and the lack of the English books.